(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The importance of using digital technologies in education has been steadily increasing, and learning through collaborative artistic projects is considered an effective method that contributes to developing artistic and academic skills. This research employs digital platforms within a creative educational environment to enhance teamwork skills among students. The study focuses on understanding how this method impacts the development of collaboration among students and improves their problem-solving and teamwork skills. The research explores the effect of learning through collaborative artistic projects using digital platforms on developing teamwork skills among students in the Fine Arts Department at the College of Basic Education, Al-Mustansiriya University. The sample consisted of 60 students selected randomly. The study follows an experimental approach, where a practical experiment was conducted on students in the Fine Arts Department using digital platforms to complete collaborative artistic projects. The students were divided into small groups and used digital tools to develop and implement their joint art projects. Data were collected through surveys, observations, and performance assessments before and after the project implementation to measure the improvement in teamwork skills. The study’s findings include: • Results showed that digital platforms enhanced students’ communication and interaction while working on artistic projects. • It was found that collaborative projects via digital platforms helped students improve their skills in cooperation, joint planning, and collective decision-making.